“Cambios del uso del suelo y dinámica territorial en el pueblo rural de Azcuénaga, Partido de San Andrés de Giles, Provincia de Buenos Aires.” - Garay, Paula Daniela (2020)
The work is focused on the rural town of Azcuénaga of the San Andrés de Giles Party, province of Buenos Aires, founded in 1880 with the inauguration of the railway station. From then on, the economic activities that were developed are basically agricultural - livestock. Over time, the political - economic crises product of neoliberalism of the 90s, caused a series of transformations that were based on the massive privatization of a large part of public assets. This had an impact on the closure of the train station and with it the closure of the fundamental means of transport for the town. This situation generates in Azcuénaga a decrease in the local population, a decrease in the traditional economy of the town, thus causing the need for a change in its economic activities. This change occurred towards the tourist reconversion, through the program "Tourist Towns" in 2008, propo sed by the government of the Province of Buenos Aires. But this change brought with it different problems linked to the lack of accompaniment by the State at the local level (Municipality of San Andrés de Giles), in investments in public works of roads, in advertising the program, in signage and insecurity . As a result of this situation, they generated a series of consequences, such as: an increase in the deterioration of the communication routes, interruption of the tranquility, added to these the disco ntent of a part of the local population.